2020
DOI: 10.1002/tcr.202000063
|View full text |Cite
|
Sign up to set email alerts
|

Directing Group Assisted Unsymmetrical Multiple Functionalization of Arene C−H Bonds

Abstract: Multiple C−H bond functionalizations promptly install diverse groups on the molecular framework and consequently fabricate complex molecular entities. This review briefly surveys the conceptual development of directing group assisted unsymmetrical multiple functionalization of arene C(sp2)−H bonds, which is exceedingly appealing and highly important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 113 publications
0
15
0
Order By: Relevance
“… , Interestingly, the desired 6,6-fused thiopyrano-isoquinoline ( 3a ) was formed in 29% yield under the catalytic conditions {[RuCl 2 ( p -cymene)] 2 (5.0 mol %), Cu­(OAc) 2 ·H 2 O (1.0 equiv), and AgSbF 6 (20 mol %) in 1,2-dichloroethane (DCE) at 120 °C for 24 h} (entry 1, Table ). Screening of acetate sources [NaOAc, KOAc, CsOAc, Mn­(OAc) 2 ·3H 2 O, Zn­(OAc) 2 ·2H 2 O, AgOAc, and anhydrous Cu­(OAc) 2 ] revealed that Cu­(OAc) 2 was most effective (entries 2–8), providing 3a in 34% yield (entry 8). , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… , Interestingly, the desired 6,6-fused thiopyrano-isoquinoline ( 3a ) was formed in 29% yield under the catalytic conditions {[RuCl 2 ( p -cymene)] 2 (5.0 mol %), Cu­(OAc) 2 ·H 2 O (1.0 equiv), and AgSbF 6 (20 mol %) in 1,2-dichloroethane (DCE) at 120 °C for 24 h} (entry 1, Table ). Screening of acetate sources [NaOAc, KOAc, CsOAc, Mn­(OAc) 2 ·3H 2 O, Zn­(OAc) 2 ·2H 2 O, AgOAc, and anhydrous Cu­(OAc) 2 ] revealed that Cu­(OAc) 2 was most effective (entries 2–8), providing 3a in 34% yield (entry 8). , …”
Section: Resultsmentioning
confidence: 99%
“…On the basis of the above mechanistic studies, the plausible mechanism is proposed (Figure ). The ligand exchange between [RuCl 2 ( p -cymene)] 2 , AgSbF 6 , and Cu­(OAc) 2 at first produces the active Ru­(II) catalyst. The coordination of the “S” moiety to the active catalyst and the activation of the proximal C–H bond of aryl thioamides forms a five-membered Ru-intermediate I .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Along these lines, the heteroatom-guided double annulation of arenes CH bonds with alkynes has been realized by the coordination of 'N' to Ru, Rh, and Ir. [14][15][16][17][18][19][20][31][32] In that respect, the coordination of amide 'N' over 'O' has granted access to polycyclic amides, wherein a metalated isoquinolone species plays a crucial role. 3337 With thioamides, such complexation of 'N' to TM over 'S' provides isoquinolones, as metalatedthioisoquinolone is prone to hydrolysis under such oxidative conditions (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple reactive sites or components may interact on each other, making it difficult to balance the reactivity and selectivity for several successive steps in one pot. In the past two decades, we have witnessed blossoming of new synthetic toolkits including C-H functionalization (Chen and Youn, 2012;Yamaguchi et al, 2012;Gulías and Mascareñas, 2016;Abrams et al, 2018;Sambiagio et al, 2018;Zheng and Hua, 2018;Ghosh et al, 2020), palladium catalysis (Chinchilla and Najera, 2014;Düfert and Werz, 2016;Trost and Min, 2020), and gold catalysis (Fürstner, 2009;Zhang et al, 2014;Dorel and Echavarren, 2015;Pflästerer and Hashmi, 2016;Marín-Luna et al, 2019). These emerging synthetic methodologies enable new cascade reaction in mild conditions via substrate activation (for alkynes, their reaction partners, or both of them), thus expanding the utilization of alkynes for syntheses of polyheterocycles with higher efficiency and diversity.…”
Section: Introductionmentioning
confidence: 99%